COMPARATIVE ANALYSIS OF POWER CONSUMPTION AND REAL-TIME PERFORMANCE BETWEEN ESP32 AND RASPBERRY PI PICO W IN IOT-BASED TEMPERATURE MONITORING SYSTEMS - Supriyanto, Supriyanto; Anggono, Sigit Umar (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
Power efficiency and real-time performance are two essential aspects in the development of Internet of Things (IoT) systems, especially for temperature monitoring applications operated continuously with limited energy resources. This study aims to compare two widely used microcontroller platforms—ESP32 and Raspberry Pi Pico W—in the context of an IoT-based temperature monitoring system using the DHT22 sensor and Wi-Fi communication. A quantitative experimental approach was employed, including measurement of average power consumption, system response time, and initial booting time over more than 100 operation cycles. The results show that Raspberry Pi Pico W consumes significantly less power (90 mA) than ESP32 (160 mA). However, ESP32 outperformed in real-time response, recording an average latency of 240 ms, while Pico W recorded 310 ms. Pico W also demonstrated faster boot time (950 ms) compared to ESP32 (1500 ms), which is beneficial in deep sleep scenarios. These findings highlight a trade-off between power efficiency and system responsiveness. This study contributes practically by providing a technical basis for selecting suitable microcontroller platforms based on application-specific needs. The results may serve as a reference for developing energy-efficient and responsive embedded systems, particularly in agriculture, healthcare, and smart home sectors.